Flyback converter rectifier choice / \c Tan Chong Wooi - Tan Chong Wooi (School of Electrical Engineering, University Malaysia Perlis, 2011)
The main purpose of this flyback converter is to design a switching power supply. It is an iterative process which involves many variables that have to be adjusted in order to obtain an optimized solution